Data rescue in selected countries in connection with the EUMETNET DARE activity. (3rd October 2021) - Chimani, Barbara; Auer, Ingeborg; Prohom, Marc; Nadbath, Mateja; Paul, Anita; Rasol, Dubravka
Abstract: In situ data are an essential need in the analyses of past and current climate change. All over the world, different data rescue activities try to extend existing time series and to retrieve data in spatial and temporal data sparse regions. Also in Europe, part of the historic data is still only available in paper archives, without any digital access to these sources. The EUMETNET Data Rescue activity was started in order to investigate the potential for additional long‐term stations, to monitor the progress of data rescue in European countries and to support participants with know‐how exchange and international connections to facilitate data exchange. The activity raised the awareness of the need for data rescue and ongoing activities. This paper will provide information on the data rescue activities of 4 EUMETNET countries focusing on different aspects and in different states of the data rescue process. While Austria, Croatia and Slovenia are connected by a partly common history which is also displayed in the history of their meteorological network, Catalonia has a different historical background. Nevertheless, the problems data rescue is confronted with are similar for all activities. Therefore, the selected countries will provide a good overview of the problems and solutions discussed during the EUMETNET meetings. This paper wants to offer insight into different strategies for data rescue as well as into ongoing activities. Moreover, the importance of cooperation in regard to data rescue is underlined and examples of possible partnerships are provided.